Rancher's forgotten rival [large type] - Yates, Maisey (Yates, Maisey. Carsons of Lone Rock, 2023)
"Welcome to Lone Rock, Oregon's Wild West. Chance Carson is the one man in Lone Rock who gets Juniper Sohappy all riled up. His family is ranching royalty. He's arrogant, insufferable and obnoxiously charming -- she'll keep her distance, thanks. But when Juniper finds him on her property, injured and without his memory, she saves his life . . . and sort of lets him believe he's her ranch hand. Making the entitled rancher work a little is one thing . . . but actually liking the man is another. Falling for him? No way. And yet the passion between them is as undeniable as it is unexpected. Will it survive the truth?"--